Influence of vibrations on hydrodynamics of melt during Bridgman crystal growth - Lyubimov, Dmitriy Victorovich; Lyubimova, Tatyana Petrovna; Ivantsov, Andrey Olegovich (Computational Continuum Mechanics, 2011)
Numerical simulation of melt flows during germanium crystal growth by the detached Bridgman method has been carried out. The study was conducted within the context of preparing an experiment on board the FOTON satellite. To suit experimental conditions, the proposed mathematical model of crystal growth processes takes into account the detachment of the crystal from the crucible wall and the existence of an additional (technological) channel in the crucible. The dependence of the intensity and structure of the melt flow on the vibration intensity and the crucible shape is studied. Resonance frequencies are determined. The analysis of system dynamics in the near-resonance region shows that the vortex generated in the technological channel can reach the crystallization front.